1989
DOI: 10.1246/cl.1989.1071
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Preparation of Alcohols from Olefins with Molecular Oxygen and Phenylsilane by the Use of Bis(acetylacetonato)cobalt(II)

Abstract: In the presence of a catalytic amount of bis(acetylacetonato)cobalt(II), various olefins react smoothly with molecular oxygen and phenylsilane at room temperature to afford the corresponding alcohols in good yields under neutral conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
174
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(188 citation statements)
references
References 4 publications
4
174
0
4
Order By: Relevance
“…With the presumed cobalt hydride catalyst generated in situ in the absence of LiBEt 3 H and Et 3 B, the alkylation of pyridine indeed proceeded to give 3 aa in 70 % yield. [20] The observed C4/C2 selectivity was similar to that in Table 1, entry 5, thus supporting the intermediacy and regeneration of the cobalthydride species [21] in the actual catalytic cycle of the reactions in Table 2. .…”
supporting
confidence: 68%
“…With the presumed cobalt hydride catalyst generated in situ in the absence of LiBEt 3 H and Et 3 B, the alkylation of pyridine indeed proceeded to give 3 aa in 70 % yield. [20] The observed C4/C2 selectivity was similar to that in Table 1, entry 5, thus supporting the intermediacy and regeneration of the cobalthydride species [21] in the actual catalytic cycle of the reactions in Table 2. .…”
supporting
confidence: 68%
“…Similar results were obtained in the garsubellin A synthesis due to an unprotected C5 prenyl group. Although Mukaiyama hydration 16 to protect the prenyl groups gave a complicated reaction mixture, treatment with m-CPBA afforded selective epoxidation. The obtained diepoxide 18 was a complex diastereomeric mixture, but the subsequent Claisen rearrangement of 18, which proceeded in moderate yield, and the critical RCM using a HoveydaeGrubbs second generation catalyst 17 successfully produced the bicyclo [3.3.1] core.…”
Section: Claisen Rearrangementering Closing Metathesis Approachmentioning
confidence: 99%
“…In addition, our model study clearly showed the importance of C5 stereochemistry to control the diastereoselectivity of the Claisen rearrangement (Scheme 5); the C5 prenyl group was a main factor in determining the conformation during the transition state and the rearrangement proceeded from the indicated face, avoiding steric repulsion between the pseudo axial methyl group at C8 and the allyl group. 20 Therefore, the actual substrate, b-prenyl 16, was converted to a-prenyl 28 before Claisen rearrangement through a deprotonation/kinetic protonation sequence (Scheme 6). Cleavage of the TMS ether, DesseMartin oxidation, and O-allylation produced 29, the precursor of the Claisen rearrangement.…”
Section: Claisen Rearrangementeintramolecular Aldol Cyclization Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreseeing potential unwanted ring closing and cross metathesis pathways, the Shibasaki group chose at this point to protect the newly installed prenyl group by masking it as a tertiary alcohol ( 50 ). This was accomplished using Mukaiyama’s 20 cobalt catalyzed hydration protocol. The resulting tertiary alcohol was then protected as a MOM-ether.…”
Section: Introductionmentioning
confidence: 99%